Effect of Low Molecular Weight Heparins and Fondaparinux Upon Thrombin Generation Triggered by Human Pancreatic Cancer Cells BXPC3 - T. Gerotziafas, Grigoris; Galea, Vassiliki; Mbemba, Elisabeth; Sassi, Mouna; Roman, Marie-Paule; Khaterchi, Amir; van Dreden, Patrick; Japcowitz, Max; Pierre Lotz, Jean; Francois Bernaudin, Jean; Fareed, Jawed; Hatmi, Mohamed; et al. (Current Vascular Pharmacology, 2014)
Low molecular weight heparins (LMWHs) and fondaparinux are widely used for prophylaxis and treatment of venous thromboembolic disease in cancer patients. However, the optimization of the antithrombotic treatment especially in patients with adenocarcinoma of the pancreas is a challenging issue. The understanding of the mechanism of action of the LMWHs and fondaparinux in cancer-induced hypercoagulability might help to optimize antithrombotic treatment. To this aim, we investigated the influence of BXPC3 pancreas adenocarcinoma cells on the antithrombotic activity of LMWHs and fondaparinux. Thrombin generation (TG) in normal platelet poor (PPP) and platelet rich plasma (PRP) spiked with clinically relevant concentrations of dalteparin, enoxaparin, nadroparin tinzaparin and fondaparinux was assessed with the Calibrated Automated Thrombogram assay. BXPC3 (5 cells/μl) were added to plasma. The mean rate index (MRI) of the propagation phase of TG and the endogenous thrombin potential (ETP) were analyzed. The IC50 of the studied compounds were determined and compared on the basis of anti-Xa and anti-IIa equivalent units. We demonstrate that the specific antithrombin (AT)-dependent anti-Xa activity of LMWHs and fondaparinux almost selectively inhibits the propagation phase of TG. The synergy between the anti-Xa and anti-IIa activities of LMWHs rather than the selective inhibition of FXa warrants abrogation of TG. The mean molecular weight and anti-Xa/anti-IIa ratio of the AT-dependent agents cannot predict the alteration of their capacity to inhibit TG. Tinzaparin was the most potent inhibitor of TG than the other LMWHs. Enoxaparin was more potent than nadroparin and dalteparin.
Keywords: fondaparinux